Plants and Flowers - Pope, Jorce; Nang ChanYeema (New York, USA Troll Associates, 1994)
Discusses how plants live, develop, and reproduce and examines such natural variatins as plants without flowers and flesh eating plants.
Keywords: Juvenile Nonfiction